Advanced TOPCon solar cells with patterned p-type poly-Si fingers on the front side and vanishing metal induced recombination losses - Hoß Jan; Kalaghichi Saman Sharbaf; Comak Mertcan; Preis Pirmin; Lossen Jan; Linke Jonathan; Koduvelikulathu Lejo Joseph; Buchholz Florian (EPJ Photovoltaics)
The silicon photovoltaic industry is rapidly expanding production capacity for TOPCon solar cells and surveys such as the ITRPV 2024 forecast worldwide market dominance for this cell concept from the year 2024 and beyond. Already now, approaches such as laser doped selective emitter and alternative methods for contact formation such as laser-enhanced contact optimization (LECO) are increasingly used in industry to reduce metal induced recombination at the cell front side. However, in order to fully avoid recombination at the front contacts the application of local passivated contacts under the metal fingers would be desirable as final evolutionary step of both-side-contacted single-junction silicon solar cells via the high-temperature route. The present paper proposes a lean fabrication process to achieve this goal and provides detailed experimental results for solar cells with polycrystalline silicon passivated contacts for both polarities. It is shown that local passivated contacts can be integrated into standard TOPCon cells by adding only a few additional process steps to the current industrial baseline process. Crucially, it is shown that this cell concept can achieve vanishing metal induced charge carrier recombination with differences below 2 mV between implied open-circuit voltage of the non-metalized cell precursor and the external open-circuit voltage of the final solar cell. In the present study this enables a champion device with an external open-circuit voltage of 719 mV and an efficiency of 23.4%. While these results mark an important milestone on the way towards a fully passivated TOPCon cell, the paper also details the challenges related to the development and integration of local passivated contacts and the shortcomings that have to be addressed in order to achieve a relevant efficiency gain over standard TOPCon cells.